Advances in marine biology. - Southward, Alan J. (Academic Press, 2003)
Advances in Marine Biology has been providing in-depth and up-to-date reviews on all aspects of Marine Biology since 1963. Volume 45 is a cumulative subject and taxonomic index volume, providing a ready guide to all research covered in volumes 20 - 44 of the series, including both eclectic and thematic volumes that examine a particular field in detail, such as 'The Biochemical Ecology of Marine Fishes' and 'Molluscan Radiation'. * Series Encompasses 40 Years of Coverage. * Cumulative Subject and Taxonomic index for Series Volumes 20- 44.